Ultrasonic Doppler Velocimetry Experiment of Lead-Lithium Flow with Oroshhi-2 Loop. (3rd October 2017) - Ueki, Yoshitaka; Noguchi, Yuya; Yagi, Juro; Tanaka, Teruya; Yokomine, Takehiko; Hirabayashi, Masaru; Ara, Kuniaki; Kunugi, Tomoaki; Sagara, Akio
Abstract: The lead-lithium eutectic alloy (PbLi) is a promising coolant for nuclear fusion reactors. Although PbLi flow and heat transfer in a nuclear fusion reactor condition needs to be comprehended, no velocity profile measurement techniques have been developed yet. Since PbLi is a high-temperature liquid metal, ultrasonic Doppler velocimetry (UDV) is a promising method. In the present study, we investigated a UDV measurement in a high-purity PbLi forced convection loop environment. In summary, naturally contained oxide particles as flow tracers could differ by PbLi purity, and this difference could influence UDV measurability.